Cognitive impairment and neuropsychiatric symptoms among individuals with history of symptomatic SARS-CoV-2 infection: a retrospective longitudinal study - Nariana Mattos Figueiredo Sousa; Ana Claudia Paradella Freitas Maranhão; Lucia Willadino Braga (Dementia & Neuropsychologia, 2024)
ABSTRACT. COVID-19 is a multisystem disease caused by the RNA virus (coronavirus 2 or SARS-CoV-2) that can impact cognitive measures. Objective: To identify the main cognitive and neuropsychiatric symptoms in adults who had no cognitive complaints prior to the infection. Specifically, to observe the trajectory of cognitive and neuropsychiatric performance after 6 months. Methods: This is a retrospective longitudinal study. Forty-nine patients (29 reassessed after 6 months), with a positive PCR test, with no prior cognitive complaints that only presented after the infection and without a history of structural, neurodegenerative or psychiatric neurological diseases. A brief cognitive assessment battery (MoCA), the Trail Making Test (TMT-A, B, ∆), and the Verbal Fluency Test were used, as well as the scales (Hospital Anxiety and Depression Scale-HADS, Fatigue Severity Scale-FSS). Correlation tests and group comparison were used for descriptive and inferential statistics. Level of significance of α=5%. Results: Mean age of 50.4 (11.3), 12.7 (2.8) years of education, higher percentage of women (69.8%). No psycho-emotional improvement (depression and anxiety) was observed between the evaluations, and patients maintained the subjective complaint of cognitive changes. The HAD-Anxiety scale showed a significant correlation with TMT-B errors. The subgroup participating in cognitive stimulation and psychoeducation showed improvement in the global cognition measure and the executive attention test. Conclusion: Our results corroborate other studies that found that cognitive dysfunctions in post-COVID-19 patients can persist for months after disease remission, as well as psycho-emotional symptoms, even in individuals with mild infection. Future studies, with an increase in casuistry and control samples, are necessary for greater evidence of these results.